Consolidated standards of reporting trials of social and psychological interventions: CONSORT-SPI - Montgomery, Paul (UK Data Service, 2015)
This collection involves data from a project to develop Consolidated Standards of Reporting Trials of Social and Psychological Interventions: CONSORT-SPI. Namely, two phases of the project involved the collection of new data: an online Delphi process and a consensus meeting. The online Delphi process aimed to develop and refine a prioritised list of reporting items to consider for a new guideline for social and psychological intervention trials. A secondary objective was to engage a wide group of stakeholders internationally at an early stage in the CONSORT-SPI project. Delphi participants were identified using a multistep, iterative approach and met pre-specified eligibility criteria as researchers, practitioners, policy-makers, journal editors, researcher funders, and/or representatives of intervention service users. Participants were asked to rate concepts, identified from the review of reporting standards in the last chapter, for importance in a guideline for reporting social and psychological intervention trials. In Round 1, participants ranked the degree of importance of 77 proposed guideline items on a scale of 1 to 10, with higher scores indicating higher importance for social and psychological intervention trials. In Round 2, participants ranked whether remaining items not reaching consensus in Round 1 should be included or excluded in a set of minimum reporting standards for these trials. In both rounds, participants had the opportunity to comment on proposed items and nominate items that may be missing from the surveys. The median, inter-percentile range, and counts of rankings for each item - in addition to participants’ comments - were used to measure consensus. The purpose of the consensus meeting was to discuss and select items for the CONSORT-SPI checklist. A group of 31 researchers, journal editors, and funders met in March 2014 to extend the CONSORT 2010 Statement to RCTs of social and psychological interventions. A three-day consensus development conference was held to discuss preliminary research on social and psychological intervention RCTs, vote on items for the CONSORT-SPI reporting standards checklist, and discuss a dissemination and implementation plan for the CONSORT-SPI guidelines. In addition to the data, the related resources provided include links to the project website and related project manuscripts. This project will develop and disseminate a guideline for reporting experiments of psychological, social, and environmental interventions. To coordinate and publicise the initiative, Steering Group of experts in core social science disciplines has been assembled. With their guidance, we will first conduct an international Delphi process with researchers, journal editors, and other stakeholders to generate a list of important reporting standards to consider for inclusion in the guideline. Results from two reviews we have conducted indicate that publications often omit information that would allow readers to assess internal validity (eg blinding and level of randomisation). Such reports may overestimate intervention effects by as much as 30 per cent. Secondly, reports should include more information relevant to the external validity of experiments (eg participant selection, intervention implementation). We will then host a consensus meeting to finalise the list of minimal reporting standards for inclusion in the guideline.The outputs from this project will help authors write clear reports, create a framework for reviewers to assess publications, expedite funding evaluations, provide a pedagogical tool for understanding these experiments, and help consumers evaluate study validity and applicability. In these ways, the guideline will facilitate efficient and effective transfer of research evidence into real-world use.